2014
DOI: 10.1007/s10548-014-0401-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Posterior Alpha Activity by Spatial Attention Allows for Controlling A Continuous Brain–Computer Interface

Abstract: Here we report that the modulation of alpha activity by covert attention can be used as a control signal in an online brain-computer interface, that it is reliable, and that it is robust. Subjects were instructed to orient covert visual attention to the left or right hemifield. We decoded the direction of attention from the magnetoencephalogram by a template matching classifier and provided the classification outcome to the subject in real-time using a novel graphical user interface. Training data for the temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…These should also integrate stimuli patterns designed to test additional types of attentional processes, rather than only exogenous attention. The fact that enhanced desynchronization is coupled with relatively preserved performance, suggesting the presence of compensatory mechanisms, is consistent with the proposal that training alpha modulation by means of Brain Computer Interface and Neurofeedback approaches are worthy endeavors [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 85%
“…These should also integrate stimuli patterns designed to test additional types of attentional processes, rather than only exogenous attention. The fact that enhanced desynchronization is coupled with relatively preserved performance, suggesting the presence of compensatory mechanisms, is consistent with the proposal that training alpha modulation by means of Brain Computer Interface and Neurofeedback approaches are worthy endeavors [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 85%
“…These effects may be explained by a mechanism where localized alpha oscillations act as an inhibitory gate for sensory processing [31]. Furthermore, several studies reported that NFB control of parietal alpha oscillations may be mastered by healthy participants [7, 32], thereby altering visuospatial bias [33] and inducing lasting increases in cortical excitability [34]. …”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings of Hanslmayr et al ( 2007 ) and van Dijk et al ( 2008 ), there are two examples that set up an online experiment based on occipital alpha bandpower features. Tonin et al ( 2013 ) using EEG data and Horschig et al ( 2014b ), who employed MEG signals, both decoded covert visual attention in a closed-loop experiment by utilizing single-trial feedback on the detected attention shift. However, both groups did not fully close the loop e.g., by manipulating the perception performance, which may have been possible by selecting suitable brain states for stimulation.…”
Section: Introductionmentioning
confidence: 99%